Respuesta :

Heyy there! I am AncientEnigma29 and I will be answering your question step by step

Step 1:

[tex] \sf \: f(x) = ln(x)[/tex]

Replace f(x) with y

[tex] \sf \: y = ln(x)[/tex]

Step 2:

Swap x and y with each other

[tex] \tt \: x = ln(y)[/tex]

Step 3:

Solve for y...

  • To do this we need to write x=ln(y) in exponential form.
  • Recognize that ln(y) is a logarithm with base e, where e has approximate value of 2.71828.

[tex] \bf \: ln(y) = log e (y)[/tex]

Rule of log used: [tex] \boxed{ \rm \:c = log_{a}b \: then \: {a}^{c} = b }[/tex]

By the rule we have, x=ln(y) is equal to y=e^x

Step 4:

Replace y with f^-1 (x)

[tex] \mathcal{ {f}^{ - 1}(x) = {e}^{x} }[/tex]